Upaya Kepala Madrasah dalam Mengembangkan Lembaga Pendidikan di Madrasah Ibtidaiyah Nashriyah Desa Tanjung Baru - Hidayat Hidayat; Ibrahim Ibrahim (Program Magister Manajemen Pendidikan Islam Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2019)
This study aims at determining the efforts of the Head of Madrasah Ibtidaiyah (MI), to find out the development of MI Nashriyah under the leadership of the current head of MI Nashriyah, Tanjung Baru Village, Tanjung Lubuk District, Ogan Komering Ilir Regency. This research is a descriptive study using a qualitative approach. Data collection methods used included: a) interviews, b) observation, and c) documentation. The data were collected through the three techniques which were organized, interpreted, and analyzed repeatedly, then analyzed with data analysis techniques. Furthermore, the credibility of the data was checked by using the data validity test, namely, triangulation. The findings in this study are: the efforts done by the head of Madrasah Ibtidaiyah Nashriyah in developing this institution covered the provision of facilities and infrastructure, such as adding student learning facilities, repairing and adding building for student learning, providing special transportation to pick up students. The development of MI Nashriyah under the leadership of the current Head of Ibtidaiyah Nashriyah Madrasah, is that the existence of a special service for students who have not been able to read the Al-Qur'an (BTA) properly and correctly, and the increase of the number of new students each year, periodical supervision on teachers during the process of learning, the increase of student academic achievement, and the increase of the number ofteaching staffs (teachers)